Concentration Kinetics of Serum MMP-9 and TIMP-1 after Blunt Multiple Injuries in the Early Posttraumatic Period. (27th March 2012) - Brumann, M.; Kusmenkov, T.; Ney, L.; Kanz, K.-G.; Leidel, B. A.; Biberthaler, P.; Mutschler, W.; Bogner, V.
Abstract : Metalloproteinases are secreted in response to a variety of inflammatory mediators and inhibited by tissue inhibitors of matrixmetalloproteinases (TIMPs). Two members of these families, MMP-9 and TIMP-1, were differentially expressed depending on clinical parameters in a previous genomewide mRNA analysis. The aim of this paper was now to evaluate the posttraumatic serum levels and the time course of both proteins depending on distinct clinical parameters. 60 multiple traumatized patients (ISS > 16) were included. Blood samples were drawn on admission and 6 h, 12 h, 24 h, 48 h, and 72 h after trauma. Serum levels were quantified by ELISA. MMP-9 levels significantly decreased in the early posttraumatic period (P < 0.05 ) whereas TIMP-1 levels significantly increased in all patients (P < 0.05 ). MMP-9 and TIMP-1 serum concentration kinetics became manifest in an inversely proportional balance. Furthermore, MMP-9 presented a stronger decrease in patients with severe trauma and non-survivors in contrast to minor traumatized patients (ISS ≤ 33) and survivors, initially after trauma.